Educational Decentralization and Curriculum Implementation Consistency: A Managerial Perspective from Indonesia - Maharani Lintang Corneasari (Multidisciplinary Journal of Social Sciences and Humanities, 2025)
Indonesia has implemented an educational decentralization policy for over two decades, aiming to enhance educational quality through greater autonomy at the regional and school levels. However, the consistent implementation of the national curriculum across diverse regions remains a major challenge. This study explores the managerial dynamics behind curriculum implementation in the context of decentralization, focusing on how school leaders and local education authorities navigate shifting national policies and localized capacities. Using a qualitative case study approach, data were collected through semi-structured interviews with school principals, curriculum coordinators, and education officials across multiple provinces. The findings reveal that inconsistencies in curriculum implementation are largely influenced by disparities in managerial competencies, access to training, and support systems at the local level. While decentralization provides flexibility, it often leads to uneven interpretations and applications of curriculum guidelines. Moreover, frequent curriculum reforms at the national level create additional pressures on school management, particularly in schools located in rural or under-resourced areas. This study highlights the need for a more robust managerial support system within the decentralized framework. Strengthening leadership training, improving coordination between central and local authorities, and providing clearer implementation guidelines are critical to achieving curriculum consistency. The findings offer practical insights for policymakers and educational leaders in Indonesia and other developing countries grappling with similar decentralization challenges. A balanced approach to autonomy and standardization is essential to ensure that educational equity and quality are upheld across the nation.